2011
DOI: 10.1080/0312407x.2011.573859
|View full text |Cite
|
Sign up to set email alerts
|

“Egg Donor Wanted”: Social Work with Women Looking for an Egg Donor

Abstract: Women seeking fertility treatment using donor eggs can face challenges associated with recruiting suitable egg donors and negotiating the role that the donor may play in the life of the child. Social work in infertility clinics is an emerging area of practice and social work counsellors have an important role to play with parties involved in the egg donation process. This paper seeks to raise awareness of social work practice with women seeking egg donors, providing an overview of issues for social work practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…[ 1 ] The views of embryo donors and recipients can complicate the designing and planning of the embryo donation process[ 7 8 ] and social and ethical complications regarding embryo donation require the determination of its complete meaning from the view of donors and recipients. [ 9 ] The results of previous studies on the attitudes of donor and recipient couples during the embryo donation process have shown that anonymity of the donor and confidence in sharing genetic's history and couples' personality characteristics are more important than physical characteristics, screening tests,[ 10 ] the possibility of future contact with the child, and received fee. [ 11 ] The attitude of embryo donors and recipients can be a foundation for the development of policy-making and decision-making regarding this program.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] The views of embryo donors and recipients can complicate the designing and planning of the embryo donation process[ 7 8 ] and social and ethical complications regarding embryo donation require the determination of its complete meaning from the view of donors and recipients. [ 9 ] The results of previous studies on the attitudes of donor and recipient couples during the embryo donation process have shown that anonymity of the donor and confidence in sharing genetic's history and couples' personality characteristics are more important than physical characteristics, screening tests,[ 10 ] the possibility of future contact with the child, and received fee. [ 11 ] The attitude of embryo donors and recipients can be a foundation for the development of policy-making and decision-making regarding this program.…”
Section: Introductionmentioning
confidence: 99%